DAMPAK INDUSTRI KREATIF DAN STRATEGI TERHADAP PENINGKATAN KESEJAHTERAAN MASYARAKAT DI KABUPATEN ACEH BESAR (STUDI PADA SUBSEKTOR INDUSTRI KERAJINAN DI KABUPATEN ACEH BESAR - Nasir Nasir; Said Muhammad (Universitas Serambi Mekkah, 2017)
This study aims to determine the impact of creative industries craft sub-sector in improving people's welfare in Aceh Besar District; The research method used in this research are: first, qualitativedescriptive analysis; second, to conduct direct interviews and fill out questionnaires by the creativeindustries industry subsector craft; The results of the research are expected for the development ofcreative economy, to provide information for local government and entrepreneurship, especially inimproving prosperity of the perpetrators in the era of ASEAN regional competition, so that thecreativity in developing entrepreneurship spirit owned by every business in Aceh Besar Regency can berealized among others : first, encouraging the growth of the creative industrial sector of the economythat can lift the image of Aceh Besar District; second, provide motivation to encourage job creation;third, encourage product innovation in the region; fourth, enhancing the competitiveness of productsproduced by groups of business units and local revenue; fifth, making local products as icons that canlift the District of Aceh Besar as a tourist destination to global and domestic markets. The resultsshowed that investment in the creative industry sub-sector of craft and creativity of creative industryentrepreneurs sub-sector craft sting has an impact on the welfare of masrakat especially for businessactors as well as the economic growth of District Aceh Great especially.